2019
DOI: 10.15766/mep_2374-8265.10848
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Intern Resilience: Individual Chief Wellness Check-ins

Abstract: Introduction: Promoting resilience is key during intern year as residents transition to becoming clinical providers. Residents consistently demonstrate a decline in empathy and an increase in burnout throughout training. Interventions involving mindfulness, stress management, and small-group discussions can reduce burnout. We created a curriculum to normalize the intern experience and provide debriefing opportunities to further improve resilience and decrease burnout. Methods: Thirty-two interns met monthly, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…However, little is known about the extent to which interns' well-being can be influenced by support provided by their senior residents, and what peer support processes may be most effective for enhancing well-being. Promisingly, one recent study suggested that regular well-being check-ins with chief residents may normalize the intern experience and help interns manage stress 14 . To better understand the specific experience of interns, we conducted a qualitative study to elucidate contributors to emotional distress and ways that peer support from senior residents may impact intern well-being in our institution's internal medicine residency program.…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about the extent to which interns' well-being can be influenced by support provided by their senior residents, and what peer support processes may be most effective for enhancing well-being. Promisingly, one recent study suggested that regular well-being check-ins with chief residents may normalize the intern experience and help interns manage stress 14 . To better understand the specific experience of interns, we conducted a qualitative study to elucidate contributors to emotional distress and ways that peer support from senior residents may impact intern well-being in our institution's internal medicine residency program.…”
Section: Introductionmentioning
confidence: 99%
“…Regular fortnightly 'check-in' sessions were conducted to elicit concerns, obtain feedback, and ensure continual wellbeing. This channel of communication was well received by interns: they appreciated faculty's concerns, had the autonomy of being able to input and contribute to the care of patients, the opportunity to air grievances confidentially and importantly, had closure on concerns they have raised regarding their rotations and training (Fischer et al, 2019). The enhanced collegiality between interns, support from seniors and improved cooperation among healthcare workers during this time of crisis naturally also contributed to reduced burnout levels, a finding well established in literature.…”
Section: Discussionmentioning
confidence: 99%
“…Several initiatives have been designed to address detachment and combat burnout by promoting social connection. Examples include reflection groups, structured social events, individual wellness check-ins by chief residents, resilience workshops, and sharing stories about patient care [6,7,8,9,10,11,12,13,14,15]. Many of these initiatives, while anecdotally beneficial, require considerable institutional resources and trainee time.…”
Section: Finding Meaning and Communitymentioning
confidence: 99%